2006 5th IEEE Conference on Sensors 2006
DOI: 10.1109/icsens.2007.355494
|View full text |Cite
|
Sign up to set email alerts
|

Robotic System for Localizing a Chemical Source Underwater by Mimicking Crayfish Behavior

Abstract: An underwater robotic system with a chemical sensing capability is proposed. Crayfish that prefer stagnant flow conditions are known to generate water currents by beating exopodites of maxillipeds to enhance the chemical perception. The developed robotic system consists of an array of electrochemical sensors and a pair of fanning devices mimicking the maxillipeds. The fanning devices beaten vertically enable the robot to draw water samples from a wide horizontal angular range and to detect the chemicals in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Each arm is waved by 90° from the outward horizontal position to the upward vertical position. The robot thus generates upward water currents, which in turn induce inflow to the sensing electrodes from the surroundings (6).…”
Section: Crayfish Robotmentioning
confidence: 99%
See 1 more Smart Citation
“…Each arm is waved by 90° from the outward horizontal position to the upward vertical position. The robot thus generates upward water currents, which in turn induce inflow to the sensing electrodes from the surroundings (6).…”
Section: Crayfish Robotmentioning
confidence: 99%
“…Our goal is to develop an underwater robot that can autonomously accomplish chemical source localization tasks under stagnant flow conditions. In our previous paper, we reported a robotic system having four chemical sensors and a pair of arms mimicking the maxillipeds of a crayfish (6). Experimental results showed that the flow field generated by waving of the maxilliped arms draws a chemical from the surroundings and thus the chemical reception at the sensors is enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…The robot is not only equipped with an array of chemical sensors, but also can actively generate water currents to enhance chemical reception by drawing surrounding water samples to the sensors. We previously reported a robot head equipped with electrochemical sensors and maxilliped arms [5], but now the head part is mounted on a submersible autonomous mobile robot. Experimental results are presented to show that the flow field generated by waving maxilliped-like arms is more effective in enhancing chemical reception than that generated by a pump.…”
Section: Introductionmentioning
confidence: 99%